Cultural Differences in Professional Help Seeking: A Comparison of Japan and the U.S. - Mojaverian, Taraneh; Hashimoto, Takeshi; Kim, Heejung S. (Frontiers in Psychology, 2013)
Previous research has found cultural differences in the frequency of support seeking. Asians and Asian Americans report seeking support from their close others to deal with their stress less often compared to European Americans. Similarly, other research on professional help seeking has shown that Asians and Asian Americans are less likely than European Americans to seek professional psychological help. Previous studies link this difference to multitude of factors, such as cultural stigma and reliance on informal social networks. The present research examined another explanation for cultural differences in professional help seeking. We predicted that the observed cultural difference in professional help seeking is an extension of culture-specific interpersonal relationship patterns. In the present research, undergraduate students in Japan and the United States completed the Inventory of Attitudes toward Seeking Mental Health Services (IASMHS), which measures professional help seeking propensity, psychological openness to acknowledging psychological problems, and indifference to the stigma of seeking professional help. The results showed that Japanese reported greater reluctance to seek professional help compared to Americans. Moreover, the relationship between culture and professional help seeking attitudes was partially mediated by use of social support seeking among close others. The implications of cultural differences in professional help seeking and the relationship between support seeking and professional help seeking are discussed.